(untitled) (Interdisciplinary Studies Journal, 2025)
Artificial Intelligence (AI) is no longer a vision of the future but a constant presence that shapes the way we live, work, and learn. Its impact on education is profound, as it opens new possibilities for rethinking pedagogical practices and engaging students in more dynamic, collaborative, and meaningful ways. AI is capable of analyzing large volumes of data, personalizing learning, optimizing teachers’ time, and preparing students for the challenges of the 21st century by developing skills such as critical thinking and problem-solving. In this context, the project “AI in Action: Smart Solutions for Real-World Challenges” aimed to analyze the potential of Information and Communication Technologies (ICT), with an emphasis on Artificial Intelligence (AI), as a support tool in the teaching and learning process, fostering student agency and promoting the teacher’s role as a facilitator in this process. This qualitative study, exemplified by a Science Fair, demonstrated that the practical application of AI stimulated students’ creativity, collaboration, and critical thinking, confirming their engagement and the public’s receptiveness, while also reinforcing the role of AI in assisting teachers and transforming schools into environments of collaboration and innovation.